Foreign students’ satisfaction on visa processing: comparison between public and private universities / Azian Mohamed Kassim...[et al.] - Mohamed Kassim, Azian; Abdul Ghani, Nadiah Maisarah; Abdul Sukor, Syuhairah; Ahmad, Jasmine (2010)
The focus of this study was to measure the foreign student’s satisfaction on visa processing services rendered by public universities compared to private universities. Ministry of Higher Education aspires to develop Malaysia as a hub for education thus welcoming foreign student is a priority. One important requirement for foreign student to stay legally in Malaysia as a student is to have student visa. The visa processing service for foreign students in public university differ from the private universities in terms of fees, time period and other requirement of services. The disparity in service levels between these two entities suggests that there could be a difference in orientation towards visa processing service. In consequence, this could also have an impact towards the satisfaction of the recipients of this service. The respondents to this research involved both students from private and public universities and it explored their level of satisfaction towards the services provided. This study hopes to give an insight on the differences that exists and identify the strengths and weaknesses that could be shared and be used as a reference towards the improvement of the overall service levels of Malaysian universities.